BULLETIN - New Sunday Times, , (New Sunday Times, 2014)
The College of Arts & Sciences, Universiti Utara Malaysia is organising the Seventh Knowledge Management International Conference (KMICe) 2014 from Aug 12-15 in Langkawi.For details, visit www.kmice.uum.edu.my/